Casamento intercultural e suas peculiariedades : um estudo sobre brasileiras que vive na Suíça - Schuler, Flávia de Maria Gomes (2011)
This dissertation aims to analyze and identify the process of migration of Brazilian women to Switzerland who came to marry with Swiss men and the repercussions of this marriage in their lives. In this perspective were considered the aspects related to the motivations for the migration and the difficulties at the arrival; the circumstances at meeting their husbands; the adaptation to the country, to the family in law and to the marriage itself; and finally the feelings experienced and the needs felt. The research is divided into three articles, one theoretical and two empirical. The first one presents a brief historical uprising about marriage and the transformation this institution has been suffering a long time. The second article searches to investigate the motivations of the migration and how the participants came to marry. The third article studies the intercultural marriage between Brazilian women and Swiss men, and the repercussions of this marriage in their lives. The methodology was based in a qualitative approach. Twelve Brazilian women who are married with Swiss men and live in Switzerland in the German part were interviewed. The appreciation of the data was realized with Minayo´s Content Analysis. The results indicate that the motivations for the migration of the participants are related to the search of better life opportunities or for falling in love with a Swiss. Some married for staying in the country, other married because of love. Nevertheless, in general, the difficulties found in marriage were similar: difficulties with the language, swiss way of thinking, children education, religion and relatives